2010
DOI: 10.1007/s00705-010-0659-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of HIV-1 RNA forms in the plasma of patients undergoing successful HAART

Abstract: An assay to characterize plasma human immunodeficiency virus 1 (HIV-1) sequences for patients with low viral loads was developed by combining the selective binding of anti-CD44 MicroBeads with a nested RT-PCR targeting the env C2V4 region. Sequences were obtained from 10 of 20 HIV+ patients who had viral loads below 48 copies/ml. Sequences derived from plasma were compared to those from CD14+ CD16 +monocytes and CD4+ T cells. The plasma sequences were most closely related to those amplified from monocytes, sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…Previous studies showed that the proportion of circulating CD16 + monocytes expands in a number of inflammatory conditions [79,80] and with HIV and SIV infection [45,46]. CD16 + monocytes in vivo and in vitro are more permissive for HIV infection when compared to CD16 − monocytes [81] and HIV is detected in CD14 + CD16 + monocytes from infected individuals undergoing successful cART [82]. In a recent study, CD14 low CD16 + and CD14 + CD16 + monocytes were shown to express distinct phenotypic and functional characteristics, including unique patterns of chemokine receptor expression and cytokine production in response to bacterial and viral pathogens [83].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that the proportion of circulating CD16 + monocytes expands in a number of inflammatory conditions [79,80] and with HIV and SIV infection [45,46]. CD16 + monocytes in vivo and in vitro are more permissive for HIV infection when compared to CD16 − monocytes [81] and HIV is detected in CD14 + CD16 + monocytes from infected individuals undergoing successful cART [82]. In a recent study, CD14 low CD16 + and CD14 + CD16 + monocytes were shown to express distinct phenotypic and functional characteristics, including unique patterns of chemokine receptor expression and cytokine production in response to bacterial and viral pathogens [83].…”
Section: Discussionmentioning
confidence: 99%
“…We propose that there is a specific subpopulation of maturing monocytes in the circulation that will soon cross the vasculature, and that these cells are infectable by HIV. Several studies indicate that monocytes prone to HIV infection include a CD16 + subset(s) [81,82]. The subpopulation(s) of monocytes susceptible to HIV infection is so small it is difficult to study in freshly isolated monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…A 525 bp fragment containing the HIV-1 env C2-V4 variable region was amplified by RT-PCR and nested PCR using primers against the conserved regions C2 and C4 (forward primer: 5′-CTGTTAAATGGCAGTCTAGC-3′; reverse primer: 5′-TGATGGGAGGGGTATACATT-3′ [43]. The PCR-amplified product was verified by agarose gel electrophoresis, gel-purified, and cloned into cloning vector pCR2.1 (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…Viral reservoirs represent a continuous burden because of their ability to replenish the viral pool as a means of inducing persistent infection. For example, in some patients, C2V3 plasma variants have been recovered despite those patients having undergone successful therapy (76). Reactivation of HIV-1 strains occurs because of therapy failure or after antiretroviral treatment interruption (77).…”
Section: Hiv-1 Cns Viral Reservoirs and Combined Antiretroviral Theramentioning
confidence: 99%